HEART RATE VARIABILITY IN PATIENTS WITH CHRONIC HEART FAILURE AND METABOLIC SYNDROME - Atakhodjaeva Gulchekhra Abdunabievna; Rakhimova Dilorom Alimovna (Modern American Journals, 2026)
The features of heart rate variability in patients with chronic heart failure were analyzed depending on the presence of metabolic syndrome components. 106 patients with functional class II-III chronic heart failure caused by postinfarction cardiosclerosis were examined. The study of the state of heart rate variability was carried out using Holter ECG monitoring.
Keywords: Chronic heart failure, metabolic syndrome, heart rate variability.